Fun facts : India - O'Brien, Terry (New Delhi : Rupa Publications, 2013)
Did you know?The original word for "chess' is the Sanskrit "chaturanga', meaning "four members of an army';Theargest employer in the world is the Indian Railways, employing over a million people;Salt is the first item served at a Bengali wedding reception to ensure one stands witness in case of a matrimonial dispute.These and many such informative and fascinating facts fill up the pages of Terry O'Brien's Fun Facts: India. The book covers a wide range of information related to India and its states, which is presenteducidly in order to makeearning a fun exercise for children. With "edutainment' as its motto, this collection hopes toay the foundation for creativity, problem-solving and the quest for knowledge in the minds of young readers. Full of fascinating trivia, Fun Facts: India presents a wide range of information related to India and its states. Easy-to-understand and simple to use, these books are designed to simultaneously entertain and educate the young reader.Handy and informative, the Fun Facts series are of particular interest to those interested in quizzing. Fun and engaging, the Fun Facts series will delight readers of all ages.
Keywords: Juvenile nonfiction